Degradable composite sanitary material and preparation method thereof
Patent Information
- Application Number
- CN202610935315.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2046-06-26
AI Technical Summary
本发明采用PES、PDES与PLA共聚,生成PES-PDES-PLA共聚物,通过引入柔性链段降低复合材料的脆性,提升材料的韧性和抗冲击性能;通过接枝的方式,将壳聚糖接枝到聚乳酸链段上,使复合材料基体具有良好的抗菌性能、生物相容性以及亲水性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of sanitary materials technology, specifically a biodegradable composite sanitary material and its preparation method. Background Technology
[0002] Hygiene materials mainly include personal hygiene products, medical dressings and consumables, cleaning and wiping products, protective equipment, and infant care products, covering multiple health and hygiene fields such as daily cleaning and care as well as infection control in professional medical settings. Especially in the medical field, ideal hygiene materials not only need to possess basic isolation and protection functions, but are also expected to have active antibacterial properties to enhance care effectiveness and improve user experience. Therefore, developing a biodegradable composite hygiene material with antibacterial properties is of great significance to the development of hygiene materials. Summary of the Invention
[0003] The present invention aims to provide a biodegradable composite sanitary material and its preparation method to solve the related technical problems existing in the prior art.
[0004] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows: A method for preparing a biodegradable composite sanitary material, specifically comprising: S1: Succinic acid, ethylene glycol, diethylene glycol, isopropyl titanate catalyst and terminal lactic acid oligomer are mixed and reacted to obtain succinic acid diol ester-lactic acid copolyester (PES-PDES-PLA). S2: Chitosan oligomer, L-lactide and stannous octoate catalyst are mixed and reacted to obtain chitosan-grafted polylactic acid (CS-g-PLA). S3: Nano zinc oxide, vinyltriethoxysilane, methacryloyloxyethyltrimethylammonium chloride and ammonium persulfate are mixed and reacted to obtain nano zinc oxide@quaternized silane (ZnO@VTES-DMC). S4: PES-PDES-PLA, CS-g-PLA, ZnO@VTES-DMC, epoxy chain extender and antioxidant are mixed, granulated by twin-screw extrusion, melted and sprayed out by meltblown die to obtain composite sanitary material matrix; S5: The composite sanitary material matrix is sequentially added to a dopamine-tannic acid-zinc finishing solution and a genipin aqueous solution for impregnation, and then dried to obtain a biodegradable composite sanitary material.
[0005] Furthermore, the preparation method of the PES-PDES-PLA is as follows: Under nitrogen protection, succinic acid, ethylene glycol, diethylene glycol and the catalyst isopropyl titanate are mixed and heated to 170-180℃, stirred at 300-400 rpm for 3-4 hours. Then, terminal hydroxyl lactic acid oligomers are added, and the temperature is raised to 180-190℃ for 1-1.5 hours. Finally, the temperature is raised to 190-200℃, the vacuum is drawn to 50-100 Pa, and the reaction is stirred for 2-3 hours. After the reaction is completed, the mixture is cooled to obtain PES-PDES-PLA.
[0006] Further, by mass, the PES-PDES-PLA comprises 64-74 parts succinic acid, 22-32 parts ethylene glycol, 10-20 parts diethylene glycol and 100-120 parts terminal hydroxyl lactic acid oligomer.
[0007] The preparation method of hydroxyl-terminated lactic acid oligomers is as follows: Under nitrogen protection, L-lactic acid and stannous octoate catalyst were mixed, heated to 140-150℃, and reacted at 300-400 rpm for 2-3 hours. Ethylene glycol was added, the temperature was raised to 160-170℃, and the reaction was continued with stirring for 1-1.5 hours to obtain terminal hydroxyl lactic acid oligomers. The mass ratio of L-lactic acid, ethylene glycol, and catalyst stannous octoate is (96-116):(4-6):(0.05-0.1).
[0008] Under the action of a catalyst, L-lactic acid undergoes a condensation reaction, with ethylene glycol acting as the end-capping agent, generating a lactic acid oligomer structure with hydroxyl groups at both ends. Subsequently, polyester segments formed by the copolymerization of succinic acid with ethylene glycol and diethylene glycol undergo transesterification and condensation reactions with the hydroxyl-terminated lactic acid oligomers, generating a PES-PDES-PLA copolymer. In the copolymer, the flexible PES / PDES segments can absorb and dissipate energy, providing intrinsic toughness to the composite material. Simultaneously, the introduction of flexible segments disrupts the regular structure of the PLA segments, reducing the brittleness of the material and improving its toughness and impact resistance. Furthermore, the PDES segments contain ether bonds, improving the hydrophilicity of the composite material. Introducing PES / PDES segments not only improves the melt viscosity of the composite material but also broadens its temperature processing range, facilitating the molding of the composite material. The introduced PES / PDES segments all contain hydrolyzable ester bonds, and the flexible segments disrupt the regularity of the polymer segments, contributing to improved degradation performance of the composite material.
[0009] Furthermore, the preparation method of the CS-g-PLA is as follows: Chitosan oligomers and L-lactide were added to dimethylacetamide and stirred until homogeneous. The mixture was then evacuated to 50-100 Pa and maintained for 0.5-1 h. Nitrogen gas was then introduced, and under nitrogen protection, stannous octoate catalyst was added. The mixture was heated to 100-110 °C and stirred at 300-400 rpm for 6-8 h. After the reaction was completed, the mixture was transferred to deionized water at 0-5 °C to precipitate. The precipitate was redissolved and extracted with dichloromethane, then rotary evaporated and vacuum dried at 40-50 °C for 10-12 h to obtain CS-g-PLA.
[0010] Furthermore, the preparation ratio of the chitosan oligomer, L-lactide, and catalyst stannous octoate is (5-7):(50-60):(0.1-0.15).
[0011] The preparation method of chitosan oligomers is as follows: Chitosan was added to deionized water, and the pH was adjusted to 4-5. The mixture was stirred at 20-30℃ and 300-400 rpm for 1-2 hours. Hydrogen peroxide aqueous solution was added, and the temperature was raised to 60-70℃. The mixture was stirred for another 4-5 hours. After stirring, the pH was adjusted to neutral. The mixture was dialyzed through a dialysis bag. The dialysate was concentrated under reduced pressure and then transferred to ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried under vacuum at 40-50℃ for 10-12 hours to obtain chitosan oligomers.
[0012] First, chitosan is degraded by hydrogen peroxide under acidic conditions, selectively breaking the glycosidic bonds in its long-chain structure to generate oligomers containing a large number of active amino and hydroxyl groups. Subsequently, under the action of a catalyst, the active amino and hydroxyl groups of the chitosan oligomers initiate the ring-opening polymerization of L-lactide, forming polylactic acid segments grafted with chitosan. By grafting chitosan onto polylactic acid segments, the composite matrix possesses good antibacterial properties, biocompatibility, and hydrophilicity. Furthermore, both CS-g-PLA and PES-PDES-PLA contain PLA segments. During mixing, the PLA segments diffuse and entangle with each other, achieving good compatibility. This not only inhibits performance degradation caused by phase separation but also triggers more energy dissipation mechanisms when the material is subjected to impact, thus significantly improving its toughness and tear resistance while maintaining its rigidity. In addition, the introduced chitosan segments increase the hydrophilicity and hydrolysis sites of the composite material, which helps promote its degradation.
[0013] Furthermore, the preparation method of the ZnO@VTES-DMC is as follows: Vinyltriethoxysilane was added to an aqueous ethanol solution and stirred until homogeneous. The pH was adjusted to 4-5 to obtain a silane solution. Nano zinc oxide was added to anhydrous ethanol and stirred until homogeneous. The silane solution was then added, and the mixture was stirred at 70-80℃ and 300-400rpm for 6-8 hours. After the reaction was completed, the mixture was cooled, centrifuged, and the precipitate was redispersed in deionized water to obtain a nano zinc oxide@silane dispersion. Under nitrogen protection, methacryloyloxyethyltrimethylammonium chloride and ammonium persulfate were added to an ethanol aqueous solution, stirred until homogeneous, and ultrasonically dispersed for 20-30 min. Subsequently, they were added to a nano zinc oxide@silane dispersion, heated to 70-80℃, and stirred at 300-400 rpm for 6-8 h. After the reaction was completed, the mixture was cooled, centrifuged, and the product was washed with anhydrous ethanol and deionized water and vacuum dried at 40-50℃ for 10-12 h to obtain ZnO@VTES-DMC.
[0014] Furthermore, the mass ratio of the nano zinc oxide, vinyltriethoxysilane, methacryloyloxyethyltrimethylammonium chloride, and ammonium persulfate is (10-15):(3-7):(10-20):(0.5-0.7).
[0015] Under acidic conditions, the silanol groups from the hydrolysis of vinyltriethoxysilane condense with nano-zinc oxide to form Si-O-Zn covalent bonds. The nano-zinc oxide is then coated with an organosilane layer terminated in vinyl groups. Subsequently, the vinyl groups react further with methacryloyloxyethyltrimethylammonium chloride to form an organosilicon layer containing quaternary ammonium salt cations on the surface of the nano-zinc oxide. This organosilicon layer not only effectively prevents the aggregation of nanoparticles through steric hindrance, allowing them to be stably dispersed in water, but also improves the interfacial compatibility and stress transfer between the matrix and the inorganic filler, enhancing the strength, toughness, and durability of the composite material. The internal zinc oxide releases zinc ions and generates reactive oxygen species to achieve antibacterial function, while the external quaternary ammonium salt cations achieve antibacterial function through electrostatic adsorption. The synergistic effect of these two mechanisms results in a better antibacterial effect.
[0016] Further, by weight, the composite sanitary material matrix comprises 15-20 parts PES-PDES-PLA, 80-100 parts CS-g-PLA, 5-10 parts ZnO@VTES-DMC, 1-2 parts epoxy chain extender, and 1-2 parts antioxidant; the twin-screw extrusion process conditions include: zone 1 temperature of 160-170℃, zone 2 temperature of 170-180℃, zone 3 temperature of 175-185℃, and zone 4 temperature of 170-180℃.
[0017] Furthermore, the process conditions for the oxygen plasma treatment include: the dopamine-tannic acid-zinc finishing solution contains 10-15 g / L dopamine hydrochloride, 5-10 g / L tannic acid, and 5-10 g / L zinc chloride; and the genipin aqueous solution contains 1-3 wt% genipin.
[0018] Before immersing the composite sanitary material matrix into the dopamine-tannic acid-zinc finishing solution, the surface is treated with plasma. The plasma voltage power is set to 80-100W, the oxygen flow rate is set to 20-30sccm, and the treatment time is set to 30-40s. Oxygen plasma treatment etches oxygen-containing polar functional groups onto the surface of the composite matrix, introducing them and increasing surface energy. The matrix is then immersed in a finishing solution, where dopamine undergoes oxidative self-polymerization to form highly adhesive polydopamine. Tannic acid, as a polyphenol compound, not only tightly binds to polydopamine through π-π stacking and hydrogen bonding but also strongly coordinates with zinc ions, forming a metal-phenolic network structure. Finally, further covalent cross-linking via genipin results in a biodegradable composite sanitary material. Tannic acid possesses antibacterial and antioxidant properties, synergistically providing antibacterial functionality with zinc ions. The introduction of tannic acid and dopamine helps improve surface hydrophilicity and the biocompatibility of the composite material.
[0019] A biodegradable composite sanitary material is prepared using any of the preparation methods described above.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention uses PES, PDES and PLA copolymerization to generate PES-PDES-PLA copolymer. By introducing flexible segments, the brittleness of the composite material is reduced, and the toughness and impact resistance of the material are improved. By grafting chitosan onto polylactic acid segments, the composite matrix has good antibacterial properties, biocompatibility and hydrophilicity.
[0021] This invention uses ZnO@VTES-DMC as a filler in a composite material. The modified organosilicon layer not only effectively prevents the aggregation of nanoparticles through steric hindrance, allowing them to be stably dispersed in water, but also improves the interfacial compatibility and stress transfer between the matrix and the inorganic filler, thereby enhancing the strength, toughness, and durability of the composite material. The internal zinc oxide releases zinc ions and generates active oxygen to achieve antibacterial function, while the external quaternary ammonium salt cations achieve antibacterial function through electrostatic adsorption. The two mechanisms work synergistically to enhance the antibacterial performance of the composite material.
[0022] This invention involves immersing the composite matrix in a finishing solution. Dopamine in the solution undergoes oxidative self-polymerization to form highly adhesive polydopamine. Tannic acid, as a polyphenol compound, not only tightly binds to polydopamine through π-π stacking and hydrogen bonding, but also strongly coordinates with zinc ions, forming a metal-phenolic network structure. Tannic acid possesses antibacterial and antioxidant properties, synergistically providing antibacterial function with zinc ions. The introduction of tannic acid and dopamine helps improve the surface hydrophilicity and the biocompatibility of the composite material. Detailed Implementation
[0023] The technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the embodiments described are only some, not all, implementations of the present invention. Other implementations that can be obtained by those skilled in the art based on the embodiments of the present invention without creative effort all fall within the protection scope of the present invention.
[0024] In the following examples and comparative examples, the particle size of the nano-zinc oxide was 50 nm; the molecular weight of chitosan was 3 × 10⁻⁶. 5 The concentration of the Da;Tris buffer was 0.1 M / L and the pH was 8.0.
[0025] Example 1: A method for preparing a biodegradable composite sanitary material, specifically as follows: S1: Under nitrogen protection, 96g of L-lactic acid and 0.05g of catalyst stannous octoate were mixed and added to a reaction vessel. The temperature was raised to 140℃ and reacted at 300rpm for 2h. Then, 4g of ethylene glycol was added, the temperature was raised to 170℃, and the reaction was continued with stirring for 1h to obtain terminal hydroxyl lactic acid oligomers. S2: Under nitrogen protection, 64g succinic acid, 22g ethylene glycol, 10g diethylene glycol and 0.1g catalyst isopropyl titanate were mixed and added to another reactor. The mixture was heated to 180℃ and stirred at 300rpm for 3h. Then, 100g terminal hydroxyl lactic acid oligomer was added and the mixture was heated to 190℃ and stirred for 1h. Finally, the mixture was heated to 200℃, evacuated to 50Pa and stirred for 2h. After the reaction was completed, the mixture was cooled to obtain PES-PDES-PLA. S3: Add 10g of chitosan to 300mL of deionized water, adjust the pH to 5, stir at 30℃ and 300rpm for 1h, add 10mL of 30wt% hydrogen peroxide aqueous solution, heat to 60℃ and continue stirring for 4h, after stirring is completed, adjust the pH to neutral, dialyze with a dialysis bag with a capacity of 3500Da for 24h, concentrate the dialysate under reduced pressure and transfer it to ethanol for precipitation, filter, wash with ethanol, and vacuum dry at 40℃ for 12h to obtain chitosan oligomers; S4: Add 5g of chitosan oligomer and 50g of L-lactide to 200mL of dimethylacetamide, stir well, evacuate to 100Pa and maintain for 1h, then introduce nitrogen gas, add 0.1g of catalyst stannous octoate under nitrogen protection, heat to 100℃, stir at 300rpm for 6h, after the reaction is completed, transfer to 0-5℃ deionized water to precipitate, redissolve the precipitate and extract with dichloromethane, rotary evaporate, and vacuum dry at 40℃ for 12h to obtain CS-g-PLA; S5: Add 3g of vinyltriethoxysilane to a mixed solution of 90mL anhydrous ethanol and 10mL deionized water, stir well, adjust the pH to 5 to obtain a silane solution, add 10g of nano zinc oxide to 100mL anhydrous ethanol, stir well, add the silane solution, and stir at 75℃ and 300rpm for 6h. After the reaction is complete, cool, centrifuge, and redisperse the precipitate in 100mL of deionized water to obtain a nano zinc oxide@silane dispersion. S6: Under nitrogen protection, 10 g of methacryloyloxyethyltrimethylammonium chloride and 0.5 g of ammonium persulfate were added to a mixed solution of 50 mL of anhydrous ethanol and 50 mL of deionized water, stirred evenly, and ultrasonically dispersed for 20 min. Then, it was added to a nano zinc oxide@silane dispersion, heated to 70 °C, stirred at 300 rpm for 6 h, cooled after the reaction was completed, centrifuged, and the product was washed with anhydrous ethanol and deionized water and vacuum dried at 40 °C for 12 h to obtain ZnO@VTES-DMC. S7: Mix 80g CS-g-PLA, 15g PES-PDES-PLA, 5g ZnO@VTES-DMC, 1g epoxy chain extender ADR-4468, 0.7g antioxidant 1010 and 0.3g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain a composite sanitary material matrix; S8: Add 10g dopamine hydrochloride, 5g tannic acid and 5g zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Remove it, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material.
[0026] Example 2: A method for preparing a biodegradable composite sanitary material, specifically as follows: S1: Under nitrogen protection, 105g of L-lactic acid and 0.07g of catalyst stannous octoate were mixed and added to the reactor. The temperature was raised to 140℃ and reacted at 300rpm for 2h. Then, 5g of ethylene glycol was added, the temperature was raised to 170℃, and the reaction was continued with stirring for 1h to obtain terminal hydroxyl lactic acid oligomers. S2: Under nitrogen protection, 70g succinic acid, 28g ethylene glycol, 15g diethylene glycol and 0.1g catalyst isopropyl titanate were mixed and added to another reactor. The mixture was heated to 180℃ and stirred at 300rpm for 3h. Then, 110g terminal hydroxyl lactic acid oligomer was added and the mixture was heated to 190℃ and reacted for 1h. Finally, the mixture was heated to 200℃, evacuated to 50Pa and stirred for 2h. After the reaction was completed, the mixture was cooled to obtain PES-PDES-PLA. S3: Add 10g of chitosan to 300mL of deionized water, adjust the pH to 5, stir at 30℃ and 300rpm for 1h, add 10mL of 30wt% hydrogen peroxide aqueous solution, heat to 60℃ and continue stirring for 4h, adjust the pH to neutral after stirring, dialyze with a dialysis bag with a capacity cutoff of 3500Da for 24h, concentrate after dialysis, transfer to ethanol for precipitation, filter, wash with ethanol, and vacuum dry at 40℃ for 12h to obtain chitosan oligomers; S4: Add 6g of chitosan oligomer and 55g of L-lactide to 200mL of dimethylacetamide, stir well, evacuate to 100Pa and maintain for 1h, then introduce nitrogen gas, add 0.1g of catalyst stannous octoate under nitrogen protection, heat to 100℃, stir at 300rpm for 6h, after the reaction is completed, transfer to 0-5℃ deionized water to precipitate, redissolve the precipitate and extract with dichloromethane, rotary evaporate, and vacuum dry at 40℃ for 12h to obtain CS-g-PLA; S5: Add 5g of vinyltriethoxysilane to a mixed solution of 90mL anhydrous ethanol and 10mL deionized water, stir well, adjust the pH to 5 to obtain a silane solution, add 13g of nano zinc oxide to 100mL anhydrous ethanol, stir well, add the silane solution, and stir at 75℃ and 300rpm for 6h. After the reaction is complete, cool, centrifuge, and redisperse the precipitate in 100mL of deionized water to obtain a nano zinc oxide@silane dispersion. S6: Under nitrogen protection, 15g of methacryloyloxyethyltrimethylammonium chloride and 0.7g of ammonium persulfate were added to a mixed solution of 50mL of anhydrous ethanol and 50mL of deionized water, stirred evenly, and ultrasonically dispersed for 20min. Then, it was added to the nano zinc oxide@silane dispersion, heated to 70℃, stirred at 300rpm for 6h, cooled after the reaction was completed, centrifuged, and the product was washed with anhydrous ethanol and deionized water and vacuum dried at 40℃ for 12h to obtain ZnO@VTES-DMC. S7: Mix 90g CS-g-PLA, 17g PES-PDES-PLA, 8g ZnO@VTES-DMC, 1.5g epoxy chain extender ADR-4468, 1.0g antioxidant 1010 and 0.5g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain the composite sanitary material matrix; S8: Add 12g of dopamine hydrochloride, 7g of tannic acid and 7g of zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Remove it, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material.
[0027] Example 3: A method for preparing a biodegradable composite sanitary material, specifically as follows: S1: Under nitrogen protection, 114g of L-lactic acid and 0.1g of catalyst stannous octoate were mixed and added to the reactor. The temperature was raised to 140℃ and reacted at 300rpm for 2h. 6g of ethylene glycol was added, the temperature was raised to 170℃, and the reaction was continued with stirring for 1h to obtain terminal hydroxyl lactic acid oligomers. S2: Under nitrogen protection, 74g succinic acid, 32g ethylene glycol, 20g diethylene glycol and 0.1g catalyst isopropyl titanate were mixed and added to another reactor. The mixture was heated to 180℃ and stirred at 300rpm for 3h. Then, 120g terminal hydroxyl lactic acid oligomer was added and the mixture was heated to 190℃ and reacted for another 1h. Finally, the mixture was heated to 200℃, evacuated to 50Pa and stirred for another 2h. After the reaction was completed, the mixture was cooled to obtain PES-PDES-PLA. S3: Add 10g of chitosan to 300mL of deionized water, adjust the pH to 5, stir at 30℃ and 300rpm for 1h, add 10mL of 30wt% hydrogen peroxide aqueous solution, heat to 60℃ and continue stirring for 4h, adjust the pH to neutral after stirring, dialyze with a dialysis bag with a capacity cutoff of 3500Da for 24h, concentrate after dialysis, transfer to ethanol for precipitation, filter, wash with ethanol, and vacuum dry at 40℃ for 12h to obtain chitosan oligomers; S4: 7g of chitosan oligomer and 60g of L-lactide were added to 200mL of dimethylacetamide, stirred evenly, and vacuumed to 100Pa and maintained for 1h. Then nitrogen was introduced, and under nitrogen protection, 0.15g of stannous octoate catalyst was added. The temperature was raised to 100℃ and stirred at 300rpm for 6h. After the reaction was completed, the mixture was transferred to deionized water at 0-5℃ to precipitate. The precipitate was redissolved and extracted with dichloromethane, then rotary evaporated and vacuum dried at 40℃ for 12h to obtain CS-g-PLA. S5: Add 7g of vinyltriethoxysilane to a mixed solution of 90mL anhydrous ethanol and 10mL deionized water, stir well, adjust the pH to 5 to obtain a silane solution, add 15g of nano zinc oxide to 100mL anhydrous ethanol, stir well, add the silane solution, and stir at 75℃ and 300rpm for 6h. After the reaction is complete, cool, centrifuge, and redisperse the precipitate in 100mL of deionized water to obtain a nano zinc oxide@silane dispersion. S6: Under nitrogen protection, 20 g of methacryloyloxyethyltrimethylammonium chloride and 0.7 g of ammonium persulfate were added to a mixed solution of 50 mL of anhydrous ethanol and 50 mL of deionized water, stirred evenly, and ultrasonically dispersed for 20 min. Then, it was added to a nano zinc oxide@silane dispersion, heated to 70 °C, stirred at 300 rpm for 6 h, cooled after the reaction was completed, centrifuged, and the product was washed with anhydrous ethanol and deionized water and vacuum dried at 40 °C for 12 h to obtain ZnO@VTES-DMC. S7: Mix 100g CS-g-PLA, 20g PES-PDES-PLA, 10g ZnO@VTES-DMC, 2g epoxy chain extender ADR-4468, 1g antioxidant 1010 and 1g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain a composite sanitary material matrix; S8: Add 15g of dopamine hydrochloride, 10g of tannic acid and 10g of zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Remove it, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material.
[0028] Comparative Examples 1-4 are technical solutions based on Example 1, as detailed below: Comparative Example 1: This comparative example relates to a method for preparing a biodegradable composite sanitary material. The difference from Example 1 is that an equal mass of PES-PLA is used instead of PES-PDES-PLA. Specifically: S1: Under nitrogen protection, 64g of succinic acid, 32g of ethylene glycol and 0.1g of catalyst isopropyl titanate were mixed and heated to 180℃, stirred at 300rpm for 3h, 100g of terminal hydroxyl lactic acid oligomer was added, the temperature was raised to 190℃ and the reaction continued for 1h, and finally the temperature was raised to 200℃, the vacuum was drawn to 50Pa, and the reaction was stirred for 2h. After the reaction was completed, the mixture was cooled to obtain PES-PLA. S2: Mix 80g CS-g-PLA, 15g PES-PLA, 5g ZnO@VTES-DMC, 1g epoxy chain extender ADR-4468, 0.7g antioxidant 1010 and 0.3g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain the composite sanitary material matrix; S3: Add 10g dopamine hydrochloride, 5g tannic acid and 5g zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Take it out, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material. The preparation methods of the terminal hydroxyl lactic acid oligomer, CS-g-PLA and ZnO@VTES-DMC are the same as those in Example 1.
[0029] Comparative Example 2: This comparative example relates to a method for preparing a biodegradable composite sanitary material. The difference from Example 1 is that an equal mass of PLA is used instead of CS-g-PLA, specifically: S1: Mix 80g PLA, 15g PES-PDES-PLA, 5g ZnO@VTES-DMC, 1g epoxy chain extender ADR-4468, 0.7g antioxidant 1010 and 0.3g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain the composite sanitary material matrix; S2: Add 10g dopamine hydrochloride, 5g tannic acid and 5g zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Take it out, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material. The preparation methods for PES-PDES-PLA and ZnO@VTES-DMC are the same as in Example 1.
[0030] Comparative Example 3: This comparative example relates to a method for preparing a biodegradable composite sanitary material. The difference from Example 1 is that an equal mass of nano-zinc oxide is used instead of ZnO@VTES-DMC. Specifically: S1: Mix 80g CS-g-PLA, 15g PES-PDES-PLA, 5g nano zinc oxide, 1g epoxy chain extender ADR-4468, 0.7g antioxidant 1010 and 0.3g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain a composite sanitary material matrix; S2: Add 10g dopamine hydrochloride, 5g tannic acid and 5g zinc chloride to 1L Tris buffer solution and stir evenly to obtain dopamine-tannic acid-zinc finishing solution. Treat 20g of composite sanitary material matrix with oxygen plasma, setting the plasma voltage power to 100W, oxygen flow rate to 25sccm and treatment time to 30s. After treatment, immerse it in the dopamine-tannic acid-zinc finishing solution and stir at 30℃ and 300rpm for 12h under light-protected conditions. After stirring, transfer it to 1wt% genipin aqueous solution and stir at 40℃ and 50rpm for 2h. Take it out, wash it with deionized water, and vacuum dry it at 40℃ for 12h to obtain biodegradable composite sanitary material. The preparation methods for CS-g-PLA and PES-PDES-PLA are the same as in Example 1.
[0031] Comparative Example 4: This comparative example relates to a method for preparing a biodegradable composite sanitary material. The difference from Example 1 is that it does not impregnate with dopamine-tannic acid-zinc finishing solution and genipin aqueous solution. Specifically: S1: Mix 80g CS-g-PLA, 15g PES-PDES-PLA, 5g ZnO@VTES-DMC, 1g epoxy chain extender ADR-4468, 0.7g antioxidant 1010 and 0.3g antioxidant 168, add to a twin-screw extruder for extrusion granulation, set the temperature of zone 1 to 160℃, zone 2 to 170℃, zone 3 to 175℃ and zone 4 to 170℃ to obtain modified PLA granules, melt them and spray them out through a meltblown die to obtain a biodegradable composite sanitary material; The preparation methods of CS-g-PLA, PES-PDES-PLA and ZnO@VTES-DMC are the same as those in Example 1.
[0032] Performance testing: Mechanical property testing: Referencing "Textiles - Nonwovens - Test methods - Part 3: Determination of breaking strength and elongation at break (strip method)" (GB / T 24218.3-2010), a constant speed elongation tensile testing machine was used for testing. The strip size was set to 200mm × 50mm, and the tensile rate was 100mm / min. The breaking strength and elongation at break of the biodegradable composite sanitary material were tested.
[0033] Antibacterial test: Referring to "Evaluation of Antibacterial Properties of Textiles Part 3: Shaking Method" (GB / T 20944.3-2008), Staphylococcus aureus and Escherichia coli were selected as test strains. The sample consisted of biodegradable composite sanitary material fragments with a total weight of 0.75g and a single piece size of 5mm × 5mm. The concentration of the inoculum was 3 × 10⁻⁶. 5The antibacterial rate of the biodegradable composite sanitary material was tested by incubating at 24℃ and 150 rpm under light-protected shaking conditions for 18 hours with CFU / mL.
[0034] Degradability test: Referring to the method of "Determination of final aerobic biodegradability of materials under controlled composting conditions by measuring carbon dioxide released - Part 1: General method" (GB / T 19277.1-2025), mature compost (pH 7.0-8.0, volatile solids content >15%) was selected. The mixing ratio of sample to compost was set at 1:6, composting temperature at 58℃, compost moisture content at 50%, oxygen concentration >6%, and the test period was 180 days to test the degradation rate of the degradable composite sanitary material.
[0035]
[0036] Conclusion: Compared with Example 1, the biodegradable composite sanitary materials prepared in Comparative Example 1 (using an equal mass of PES-PLA instead of PES-PDES-PLA), Comparative Example 2 (using an equal mass of PLA instead of CS-g-PLA), Comparative Example 3 (using an equal mass of nano-zinc oxide instead of ZnO@VTES-DMC), and Comparative Example 4 (not impregnated with dopamine-tannic acid-zinc finishing solution and genipin aqueous solution) all exhibit inferior mechanical properties and antibacterial properties compared to Example 1. The biodegradable composite sanitary material provided by this invention possesses both good degradation performance and excellent antibacterial properties.
[0037] It will be apparent to those skilled in the art that the present invention is not limited to the specific details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and core features of the invention. Therefore, the above embodiments should be considered exemplary rather than restrictive in any respect. The scope of protection of the present invention is defined by the appended claims, not by the foregoing description, and is therefore intended to encompass all variations in the meaning and scope of the equivalents of the claims within the scope of the present invention.
Claims
1. A method for preparing a biodegradable composite sanitary material, characterized in that: Specifically: S1: Succinic acid, ethylene glycol, diethylene glycol, isopropyl titanate catalyst and terminal lactic acid oligomer are mixed and reacted to obtain PES-PDES-PLA; S2: Chitosan oligomer, L-lactide and stannous octoate catalyst are mixed and reacted to obtain CS-g-PLA; S3: Mix and react nano zinc oxide, vinyltriethoxysilane, methacryloyloxyethyltrimethylammonium chloride and ammonium persulfate to obtain ZnO@VTES-DMC; S4: PES-PDES-PLA, CS-g-PLA, ZnO@VTES-DMC, epoxy chain extender and antioxidant are mixed, granulated by twin-screw extrusion, melted and sprayed out by meltblown die to obtain composite sanitary material matrix; S5: The composite sanitary material matrix is sequentially added to dopamine-tannic acid-zinc finishing solution and genipin aqueous solution for impregnation, and then dried to obtain a biodegradable composite sanitary material; PES-PDES-PLA contains, by mass, 64-74 parts succinic acid, 22-32 parts ethylene glycol, 10-20 parts diethylene glycol and 100-120 parts terminal hydroxyl lactic acid oligomer; the mass ratio of chitosan oligomer, L-lactide and catalyst stannous octoate is (5-7):(50-60):(0.1-0.15).
2. The method for preparing a biodegradable composite sanitary material according to claim 1, characterized in that: The preparation method of PES-PDES-PLA is as follows: Under nitrogen protection, succinic acid, ethylene glycol, diethylene glycol and the catalyst isopropyl titanate are mixed and heated to 170-180℃, stirred at 300-400 rpm for 3-4 hours. Then, terminal hydroxyl lactic acid oligomers are added, and the temperature is raised to 180-190℃ for 1-1.5 hours. Finally, the temperature is raised to 190-200℃, the vacuum is drawn to 50-100 Pa, and the reaction is stirred for 2-3 hours. After the reaction is completed, the mixture is cooled to obtain PES-PDES-PLA.
3. The method for preparing a biodegradable composite sanitary material according to claim 1, characterized in that: The preparation method of CS-g-PLA is as follows: Chitosan oligomers and L-lactide were added to dimethylacetamide and stirred until homogeneous. The mixture was then evacuated to 50-100 Pa and maintained for 0.5-1 h. Nitrogen gas was then introduced, and under nitrogen protection, stannous octoate catalyst was added. The mixture was heated to 100-110 °C and stirred at 300-400 rpm for 6-8 h. After the reaction was completed, the mixture was transferred to deionized water at 0-5 °C for precipitation. The precipitate was redissolved and extracted with dichloromethane, then rotary evaporated and vacuum dried at 40-50 °C for 10-12 h to obtain CS-g-PLA.
4. The method for preparing a biodegradable composite sanitary material according to claim 1, characterized in that: The preparation method of ZnO@VTES-DMC is as follows: Vinyltriethoxysilane was added to an aqueous ethanol solution and stirred until homogeneous. The pH was adjusted to 4-5 to obtain a silane solution. Nano zinc oxide was added to anhydrous ethanol and stirred until homogeneous. The silane solution was then added, and the mixture was stirred at 70-80℃ and 300-400rpm for 6-8 hours. After the reaction was completed, the mixture was cooled, centrifuged, and the precipitate was redispersed in deionized water to obtain a nano zinc oxide@silane dispersion. Under nitrogen protection, methacryloyloxyethyltrimethylammonium chloride and ammonium persulfate were added to an ethanol aqueous solution, stirred until homogeneous, and ultrasonically dispersed for 20-30 min. Subsequently, they were added to a nano zinc oxide@silane dispersion, heated to 70-80℃, and stirred at 300-400 rpm for 6-8 h. After the reaction was completed, the mixture was cooled, centrifuged, and the product was washed with anhydrous ethanol and deionized water and vacuum dried at 40-50℃ for 10-12 h to obtain ZnO@VTES-DMC.
5. The method for preparing a biodegradable composite sanitary material according to claim 4, characterized in that: The mass ratio of nano zinc oxide, vinyltriethoxysilane, methacryloyloxyethyltrimethylammonium chloride and ammonium persulfate is (10-15):(3-7):(10-20):(0.5-0.7).
6. The method for preparing a biodegradable composite sanitary material according to claim 1, characterized in that: By weight, the composite sanitary material matrix includes 15-20 parts PES-PDES-PLA, 80-100 parts CS-g-PLA, 5-10 parts ZnO@VTES-DMC, 1-2 parts epoxy chain extender, and 1-2 parts antioxidant; the twin-screw extrusion process conditions include: zone 1 temperature of 160-170℃, zone 2 temperature of 170-180℃, zone 3 temperature of 175-185℃, and zone 4 temperature of 170-180℃.
7. The method for preparing a biodegradable composite sanitary material according to claim 1, characterized in that: The dopamine-tannic acid-zinc finishing solution contains 10-15 g / L dopamine hydrochloride, 5-10 g / L tannic acid, and 5-10 g / L zinc chloride; the genipin aqueous solution contains 1-3 wt% genipin.
8. A biodegradable composite sanitary material, characterized in that: It is prepared by the preparation method according to any one of claims 1-7.
Citation Information
Patent Citations
Environment-friendly high-oxygen-barrier and water-resistant modified plastic, plastic alloy and functional product of environment-friendly high-oxygen-barrier and water-resistant modified plastic
CN121108662A
Carbon fiber reinforced polylactic acid composite material and preparation method thereof
CN121517876A